Classifications of Solutions of Second Order Nonlinear Neutral Delay Difference Equations With Positive and Negative Coefficients - Thandapani, E.; Vijaya, M. (Sarajevo Journal of Mathematics, 2024)
In this paper the authors classified all solutions of the following equation Δ( a_n( Δ (x_n+c_nx_n-k)) ^α )+p_nf(x_n-l)-q_ng(x_n-m) = 0 into four classes and obtain conditions for the existence/nonexistence of solutions in these classes. Examples are provided to illustrate the results. 2000 Mathematics Subject Classification. 39A11